DEVELOPMENT OF THE "SPEAK WITH CONFIDENCE" MODULE: INTERVENTION BASED ON THE RESULTS OF IDENTIFYING ENGLISH LANGUAGE ANXIETY FACTORS IN LOW-ACHIEVING STUDENTS AT SMPN WELIMAN - Bonefantura Jemy Bria; Yofince Abatan; Yohanes Rusae; Valentinus Kopong Masan (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
English speaking anxiety is a significant psychological barrier experienced by low-achieving students, impacting low active participation and academic achievement. Based on initial observations at SMPN Weliman, it was found that 78% of students with scores below the Minimum Completeness Criteria experienced symptoms of high anxiety such as nervousness, fear of making mistakes, trembling voices, and avoiding eye contact when asked to speak English. This condition is exacerbated by the unavailability of teaching materials or special intervention programs from the school to address speaking anxiety in this student group, causing the problem to persist without systematic handling. This research, conducted in the even semester of the 2024/2025 academic year, aims to develop the "Speak with Confidence" module as an intervention based on the identification results of English speaking anxiety factors in low-achieving students at SMPN Weliman. The research method used Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 32 eighth-grade students who had low English achievement and high anxiety levels based on initial screening using the Foreign Language Classroom Anxiety Scale (FLCAS). Data collection instruments included an adapted FLCAS questionnaire, semi-structured interviews, participatory observation, and speaking performance tests. SMPN Weliman played an active role as a research partner, contributing to the initial identification of low-achieving and high-anxiety students, providing facilities, space, and time for intervention implementation, involving English teachers in practical validation of the module, and providing assistance during the program implementation process. The identification results showed three main anxiety factors: fear of making mistakes (78%), lack of confidence (72%), and limited vocabulary (68%). The "Speak with Confidence" module was developed using a scaffolding approach and integration of relaxation techniques, consisting of six progressive learning units covering self-introduction, vocabulary enrichment, constructing simple sentences, expressing ideas, dialogue practice, and mini-presentations. Expert validation results showed the module was highly feasible to use with an average score of 84.8% (very feasible category). Effectiveness test results showed a significant decrease in anxiety levels from an average of 82.3 (high category) to 45.6 (low category) and an increase in speaking performance scores from an average of 54.2 to 78.6. The paired sample t-test showed a significance of 0.000 (<0.05), proving the module's effectiveness statistically. This research concludes that the "Speak with Confidence" module is effective in reducing anxiety and improving English speaking skills of low-achieving students at SMPN Weliman. This module is recommended to be integrated into regular English learning and remedial programs as a needs-based intervention that can be applied sustainably.